Bioaccumulation Study of Cadmium and Lead in Cyprinus carpio from the Colorado River, Using Automated Electrochemical Detection - Vallese, Federico Danilo (2024)
The monitoring of heavy metals in aquatic ecosystems is of critical importance due to the toxic effects that these elements can have on wildlife and the potential risks that they pose to human health. Rivers situated in close proximity to agricultural regions are particularly susceptible to contamination from a combination of natural and anthropogenic sources. The study of bioaccumulation is of great importance for the early detection of environmental stressors. The combination of electrochemical techniques, such as square-wave anodic stripping voltammetry (SWASV), with automated flow-batch systems represents an efficient and cost-effective approach for the detection of trace metals in environmental samples. This study examines the bioaccumulation of cadmium and lead in Cyprinus carpio, a bioindicator of contamination in the Colorado River, Argentina. The fish were exposed to sublethal metal concentrations for 24, 48, and 96 h. Metal quantification was conducted using a novel automatic flow-batch system with SWASV and a bismuth film electrode. To the best of our knowledge, this constitutes the first application of this methodology on aquatic bioindicators for the assessment of metal accumulation in a natural environment. The technique demonstrated enhanced sensitivity and selectivity for the detection of trace metals. The bioaccumulation results demonstrated an increase in cadmium and lead concentrations in fish liver tissue after 96 h, reaching 10.5 µg g−1 and 11.9 µg g−1, respectively. Validation with inductively coupled plasma–atomic emission spectrometry (ICP-AES) demonstrated a satisfactory correlation, confirming the reliability of the method. This novel electrochemical approach offers enhanced accuracy and efficiency, making it a promising tool for environmental monitoring. The results indicate that Colorado River water is within safe levels for aquatic life regarding these metals. However, continuous monitoring is recommended to detect changes in contamination levels and protect ecosystem health, especially during water crises and under climate change.